The Role of Financial Inclusion in Income Inequality, Poverty Reduction & ‎Economic Growth in Developing Countries - SHAHZAD, SHAKEEL (International Journal of Islamic Economics and Governance, 2023)
This study was conducted to examine the role of financial inclusion in economic growth, poverty, and income inequality in developing countries from 2010 to 2020. A panel data consisting of 101 countries for the period 2010 to 2020 was compiled from the World Development Indicators and the Global Financial Inclusion Database (Global Findex Database). The collected data was analyzed using the System Generalized Method of Moments. The study’s findings indicate that financial inclusion has a positive impact on improving economic growth and reducing income inequality in developing countries. However, contrary to existing literature, this study found that financial inclusion has a direct relationship with poverty, which can be attributed to the economic peculiarities of developing countries. Therefore, this study concludes that financial inclusion contributes to improved economic growth and reduced income inequality. Although it may not directly alleviate absolute poverty, it helps reduce poverty through the mechanisms of income inequality and economic growth. It is recommended that policymakers and regulators in respective countries focus on expanding the scope of financial inclusion to enhance economic growth and reduce income inequality.